2015
DOI: 10.3389/fnut.2014.00028
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cisplatin Sensitivity in Human Cervical Cancer: Epigallocatechin-3-Gallate

Abstract: Cisplatin is one of the effective chemotherapeutics in the treatment of several types of cancers. However, in addition to the efforts against to its toxicity, the amelioration of cisplatin sensitivity is an important point in treatment of cervical cancer. To do so, additional substances such as epigallocatechin gallate (EGCG), a polyphenol in green tea, have been used in combination with chemotherapeutics. We aimed to investigate the possible molecular pathways to potentiate cervical cancer cell (HeLa) growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…In our previous study, we found that a combination of pyrrolidine dithiocarbamate and cisplatin synergistically increased apoptosis and inhibited cell growth by suppressing NF-κB in human cervical cancer cells. Additionally, agents including genistein, 93 curcumin, 16 tea polyphenols, 94 melatonin, 95 mifepristone, 96 – 98 epigallocatechin gallate, 99 , 100 ursolic acid, 101 Morinda citrifolia , 102 , 103 and wogonin 104 have been shown to be beneficial to overcome CPR via targeting the molecular pathways that are involved in CPR ( Table 1 ). Understanding the molecular mechanisms underlying CPR may be helpful to identify patients with a potential to develop CPR, and thus oncologists may be able to provide an effective therapy for those patients.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…In our previous study, we found that a combination of pyrrolidine dithiocarbamate and cisplatin synergistically increased apoptosis and inhibited cell growth by suppressing NF-κB in human cervical cancer cells. Additionally, agents including genistein, 93 curcumin, 16 tea polyphenols, 94 melatonin, 95 mifepristone, 96 – 98 epigallocatechin gallate, 99 , 100 ursolic acid, 101 Morinda citrifolia , 102 , 103 and wogonin 104 have been shown to be beneficial to overcome CPR via targeting the molecular pathways that are involved in CPR ( Table 1 ). Understanding the molecular mechanisms underlying CPR may be helpful to identify patients with a potential to develop CPR, and thus oncologists may be able to provide an effective therapy for those patients.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“… 23 However, two problems in cisplatin treatment are that the sensitivity needs to be improved and the cellular toxicity also increases significantly along with the increase of dosage. 24 The molecular mechanism underlying cisplatin resistance is multifactorial, and mainly associated with the following factors: 1) less accumulation of intracellular platinum compounds; 2) enhanced ability of tumor cells to repair damaged DNA; 3) upregulation of antiapoptotic proteins; and 4) enhanced epithelial–mesenchymal transition. 6 The precise mechanism of how S100A9 protein regulates cervical cancer cell sensitivity to cisplatin is poorly understood up to now.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to cisplatin in advanced and recurrent cervical cancers results in only a 10-20% chance of living through the year (Diaz-Padilla et al, 2013). As a result, substantial effort has been made to identify potential mechanisms of cisplatin resistance as well as ways to re-sensitize cervical cancer cells (Kilic et al, 2015;Roy and Mukherjee, 2014;Zhu et al, 2016). The efficacy of cisplatin is at least partially determined by gene expression patterns in cervical cancer cells, with multiple DNA repair genes being identified as important predictors of cisplatin sensitivity (Garzetti et al, 1996;Hasegawa et al, 2011;Henríquez-Hernández et al, 2011;Kitahara et al, 2002;Saito et al, 2004;Zhu et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%